2018
DOI: 10.3389/fimmu.2018.00009
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of circRNA in Tumor Immunity Regulation and Immunotherapy

Abstract: Non-coding RNAs (ncRNAs) can be divided into circular non-coding RNAs (circRNAs) and linear ncRNAs. ncRNAs exist in different cell types, including normal cells, tumor cells and immunocytes. Linear ncRNAs, such as long ncRNAs and microRNAs, have been found to play important roles in the regulation of tumor immunity and immunotherapy; however, the functions of circRNAs in tumor immunity and immunotherapy are less known. Here, we review the current status of ncRNAs in the regulation of tumor immunity and immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
262
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(267 citation statements)
references
References 105 publications
4
262
0
1
Order By: Relevance
“…Studies have shown that exon-derived circRNAs have miRNA response elements on their surface that specifically bind to miRNAs and regulate downstream gene expression. 3 At present, there are only a few research articles on the relationship between circRNA and liver disease. The existing papers mainly focus on the field of primary liver cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that exon-derived circRNAs have miRNA response elements on their surface that specifically bind to miRNAs and regulate downstream gene expression. 3 At present, there are only a few research articles on the relationship between circRNA and liver disease. The existing papers mainly focus on the field of primary liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA (circRNA) is one of the latest areas of focus in the field of non‐coding RNA (ncRNA) research. The study of circRNAs has allowed for significant advances in the elucidation of disease pathogenesis, development of diagnostic biomarkers, and development of therapeutic targets, particularly in tumor biology, but there have been very few reports on their roles in the area of liver fibrosis. This study intends to further study the role of circRNA on the pathogenesis of liver fibrosis, in order to gain new insight for future studies on liver fibrosis, and to find new strategies for liver fibrosis treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Circular RNAs (circRNAs) are new class of noncoding RNAs (ncRNAs) and are hotspot in the field of RNA . CircRNA has a high tissue‐specific expression and stable structure .…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are new class of noncoding RNAs (ncRNAs) and are hotspot in the field of RNA. 6 CircRNA has a high tissue-specific expression and stable structure. 7 CircRNA mediates gene expression at the level of posttranscription or transcription by interacting with alternative molecules.…”
mentioning
confidence: 99%